Integration of peroxisomes into an endomembrane system that governs cellular aging - Beach, Adam; Burstein, Michelle T.; Richard, Vincent R.; Leonov, Anna; Levy, Sean; Titorenko, Vladimir I. (Frontiers in Physiology, 2012)
The peroxisome is an organelle that has long been known for its essential roles in oxidation of fatty acids, maintenance of reactive oxygen species (ROS) homeostasis and anaplerotic replenishment of tricarboxylic acid (TCA) cycle intermediates destined for mitochondria. Growing evidence supports the view that these peroxisome-confined metabolic processes play an essential role in defining the replicative and chronological age of a eukaryotic cell. Much progress has recently been made in defining molecular mechanisms that link cellular aging to fatty acid oxidation, ROS turnover and anaplerotic metabolism in peroxisomes. Emergent studies have revealed that these organelles not only house longevity-defining metabolic reactions but can also regulate cellular aging via their dynamic communication with other cellular compartments. Peroxisomes communicate with other organelles by establishing extensive physical contact with lipid bodies, maintaining an endoplasmic reticulum (ER) to peroxisome connectivity system, exchanging certain metabolites, and being involved in the bidirectional flow of some of their protein and lipid constituents. The scope of this review is to summarize the evidence that peroxisomes are dynamically integrated into an endomembrane system that governs cellular aging. We discuss recent progress in understanding how communications between peroxisomes and other cellular compartments within this system influence the development of a pro- or anti-aging cellular pattern. We also propose a model for the integration of peroxisomes into the endomembrane system governing cellular aging and critically evaluate several molecular mechanisms underlying such integration.